A defamiliarisation of the naturalised usability of the Photoshop graphical user interface - Lekuntwane, Onica (My University, 2009)
ABSTRACT The graphical user interface of the ubiquitous Photoshop image manipulation software has naturalised image production as selection from a menu of pre-defined options. Before the birth of Adobe Photoshop in 1990, creative arts production was a specialised and predominantly time consuming craft. Today image production has been automated through a system that has democratised previously specialised production skills. New media theorists and practitioners have argued that the GUI has been designed as an environment to be looked through, instead of being looked at, critically. As a dominant postmodern cultural tool, Photoshop has consequently influenced the design of subversive artworks such as HeritageGold and Autoshop, which provide a platform for challenging the presumed universal appeal of the graphical user interface (GUI). Although much research has been conducted around the design of the GUI, and the user experience, there is a lack of critical writing around Photoshop as a cultural tool which has naturalised its usability for a presumably universal target audience. As an African user of technology that is based on graphical interfaces I use Photoshop to defamiliarise this naturalised interpretation and usability of software.